Návrh konstrukce kompozitního chassis vozidla Formule Student - Gregor, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Bakalářská práce se zabývá novým konstrukčním návrhem a výrobou rámu vozidla Formule student podle aktuálních pravidel se zaměřením na kompozitní část. Teoretická část je zaměřená na současně používané koncepty v této soutěži a přibližuje využití kompozitních sendvičových materiálů. Těžištěm práce je část konstrukční, kde jsou popsány nejdůležitější kroky iteračního procesu k vytvoření rámu, zejména ergonomie, bezpečnost a spojení s nápravami. Poslední část je věnována výrobnímu procesu. Výstupem této práce je funkční rám monopostu Dragon 8.

This bachelor thesis deals with structural design and manufacturing of Formula student chassis according the latest rules with primary aim to composite monocoque. In theoretic part is briefly described Formula student and the team. It shows actual used designs of chassis in competition and characteristics of composites and sandwich structures. In design section is described the design of the chassis due to safety, ergonomics and connections to other parts of the car. At the end is shown the manufacturing process of CFRP monocoque. The output of this thesis is made chassis of Dragon 8.
Design of Composite Chassis for Formule Student
Keywords: Chassis; kompozit; monokok; sendvičová struktura; prepreg; formule student; Chassis; composite; monocoque; sandwich structure; prepreg; formula student